1982
DOI: 10.1042/cs0620381
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Resistance to the Renal Action of Parathyroid Hormone in Human Vitamin D Deficiency

Abstract: 1. The response to exogenous parathyroid hormone (PTH) was tested in normal subjects and patients with osteomalacia due to vitamin D deficiency; 200 MRC units of bovine PTH were administered intravenously. 2. The rise in plasma adenosine 3':5'-cyclic monophosphate (cyclic AMP) and the increase in urinary excretion of cyclic AMP were reduced in the patients with vitamin D deficiency. After treatment with vitamin D the responses returned to normal. 3. It is suggested that this reversible resistance is due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Taken these together, it is possible that urinary cAMP response to exogenous PTH could diminish to the extent of PHP type I in some patients with severe vitamin D deficiency with markedly elevated endogenous PTH levels, as in our case 1. As suggested by others, chronic elevation in plasma PTH might induce desensitization of PTH receptors and lead to the development of hormone resistance [19,[31][32][33]. tions were higher in strict vegetarians compared with controls [36].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Taken these together, it is possible that urinary cAMP response to exogenous PTH could diminish to the extent of PHP type I in some patients with severe vitamin D deficiency with markedly elevated endogenous PTH levels, as in our case 1. As suggested by others, chronic elevation in plasma PTH might induce desensitization of PTH receptors and lead to the development of hormone resistance [19,[31][32][33]. tions were higher in strict vegetarians compared with controls [36].…”
Section: Discussionmentioning
confidence: 80%
“…He speculated that low fish normalities seen in patients with vitamin D deficiency are reversible. Lewin et al reported that the incremental responses of urinary cAMP to exogenous PTH were subnormal in most patients with vitamin D deficiency and the magnitude of responses became much greater after vitamin D repletion [19]. Kruse et al by measuring baseline urinary cAMP also suggested that the renal cAMP production in response to endogenous PTH was decreased in vitamin D deficient states [30].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The majority of these reports (5,6,9,10,(31)(32)(33) Resistance to PTH has been provoked in rats by hypercalcemia (36), hypermagnesemia (37), and hypokalemia (38), and in both rats and chicks by hypocalcemia associated with either vitamin D deficiency or a calcium-deficient diet (27,39). Humans with chronic renal failure (5, 9), vitamin D deficiency (32), and some patients with primary hyperparathyroidism (6)(7)(8)(9) are also refractory to stimulation by exogenous PTH.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike PHP type 1, the clinical mechanisms of abnormal PTH signaling in PHP type 2 remain obscure. Furthermore, it is questionable if PHP type 2 should stand as a disease entity because the results of the Ellsworth-Howard test in some patients with vitamin D deficiency and/or renal tubular damage resemble those of PHP type 2 19,[22][23][24][25] . In our patient, the clinical findings and initial laboratory results suggested PHP type 2 or PHP type 1b.…”
Section: Adult Onset Pseudohypoparathyroidismmentioning
confidence: 99%